Vagaries of osteosarcoma at a tertiary care center in Southern India - Das, Tuhina; Raghuveer CV,; Nayak, Anwesha; Sinha, Ruchi; Ghosh, Anirban (Asian Journal of Medical Sciences, 2024)
Background: Osteosarcoma (Os) is the greatest histologic mimicker of all bone tumors. We conducted a retrospective study on its various histopathological patterns, vis-à-vis, clinical and diagnostic features, highlighting its variations. Aims and Objectives: The objective of this study was to study the demographic distribution of Os presenting to our centers and appreciate the histological variations of the disease prevalent in this part of the world as such a study had not been done before. Materials and Methods: Over a period of 25 years, we encountered 100 cases of Os at our institution. The clinical details, investigative findings, gross appearance of tumor tissue obtained, and their hematoxylin and eosin-stained microscopic appearance were studied. Results: The majority were in the 2nd and 3rd decades with a male-to-female ratio of 1.8:1. Long bones were most commonly involved. Microscopically, apart from the conventional type, the histological variants encountered were small cell, soft tissue, malignant fibrous histiocytoma-like, telangiectatic, and juxtacortical including parosteal, periosteal, and dedifferentiated parosteal. Patients were treated with radical amputations, chemo-radiotherapy, and limb salvage surgeries. Conclusion: Being obvious that Os presents with a variety of presentations eluding any prediction regards its biologic behavior, the pathologist should be keen on thorough sampling of tumor tissue and correlate the histologic type with the radiological appearance and clinical presentation.